Effect of Er : YAG and diode laser irradiation on the root surface: Morphological and thermal analysis - Theodoro, Letícia Helena [UNESP]; Haypek, P.; Bachmann, L.; Garcia, V. G.; Sampaio, J.E. C.; Zezell, D. M.; Eduardo, C. D. (Amer Acad Periodontology, 2003)
Background: the aim of the present study was to compare the effects of Er:YAG and diode laser treatments of the root surface on intrapulpal temperature after scaling and root planing with hand instruments.Methods: Fifteen extracted single-rooted teeth were scaled and root planed with hand instruments. The teeth were divided into 3 groups of 5 each and irradiated on their buccal and lingual surfaces: group A: Er:YAG laser, 2.94 mum/100 mJ/10 Hz/ 30 seconds; group B: diode laser, 810 nm/1.0 W/0.05 ms/30 seconds; group C: diode laser, 810 nm/1.4 W/0.05 ms/30 seconds. The temperature was monitored by means of a type T thermocouple (copper-constantan) positioned in the pulp chamber to assess pulpal temperature during and before irradiation. Afterwards, the specimens were longitudinally sectioned, and the buccal and lingual surfaces of each root were analyzed by scanning electron microscopy.Results: In the Er:YAG laser group, the thermal analysis revealed an average temperature of -2.2 +/- 1.5degreesC, while in the diode laser groups, temperatures were 1.6 +/- 0.8degreesC at 1.0 W and 3.3 +/- 1.0degreesC at 1.4 W. Electronic micrographs revealed that there were no significant morphological changes, such as charring, melting, or fusion, in any group, although the specimens were found to be more irregular in the Er:YAG laser group.Conclusions: the application of Er:YAG and diode lasers at the utilized parameters did not induce high pulpal temperatures. Root surface irregularities were more pronounced after irradiation with an Er:YAG laser than with a diode laser.
Keywords: comparison studies; dental pulp; lasers/therapeutic use; periodontal diseases/therapy; planing; scaling; temperature